2011
DOI: 10.1192/bjp.bp.110.083808
|View full text |Cite
|
Sign up to set email alerts
|

Childhood abuse, the BDNF-Val66Met polymorphism and adult psychotic-like experiences

Abstract: Individuals exposed to childhood abuse are more likely to report positive psychotic-like experiences. Met carriers reported more positive psychotic-like experiences when exposed to childhood abuse than did individuals carrying the Val/Val genotype. Therefore, the observed gene-environment interaction effect may be partially responsible for individual variation in response to childhood abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
103
3
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(121 citation statements)
references
References 39 publications
(77 reference statements)
12
103
3
3
Order By: Relevance
“…Firstly, the present twin sample from the general population showed similar means and prevalences of psychotic experiences to those reported previously in singleton samples also using the CAPE questionnaire (3,15). In respect to childhood adversity, in a large communitybased study using the original version of the ACE questionnaire 36.1% of the sample reported 0 adverse childhood experiences, 26.0% reported one adverse childhood experience and the rest reported two or more adverse childhood experiences (38).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Firstly, the present twin sample from the general population showed similar means and prevalences of psychotic experiences to those reported previously in singleton samples also using the CAPE questionnaire (3,15). In respect to childhood adversity, in a large communitybased study using the original version of the ACE questionnaire 36.1% of the sample reported 0 adverse childhood experiences, 26.0% reported one adverse childhood experience and the rest reported two or more adverse childhood experiences (38).…”
Section: Discussionsupporting
confidence: 84%
“…These mechanisms of geneenvironment interplay may underlie previously reported associations between environmental risk factors such as childhood adversity and psychotic outcomes. Indeed, two recent studies provide evidence for gene-environment interaction effects in the association between psychosocial stress factors and psychotic experiences in samples drawn from the general population (15)(16). However, it would be also important to clarify whether environmental factors per se have an impact on the expression of psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the main aim of the present study, the prevalence of individuals exposed to childhood abuse among the FEP patients (52%) was similar to that reported for childhood physical abuse by Üçok and colleagues (40.9%) (10) which is higher than the prevalences reported for childhood adversity in non clinical samples (25% 32%) (34). The fact that individuals at psychometric risk for psychosis (High CAPE group) also presented a high prevalence of childhood abuse is in accordance with previous research, although others have found even higher prevalences (35).…”
Section: Discussionsupporting
confidence: 87%
“…Alemany et al (2011) recently documented the first allelic association with psychotic symptoms, demonstrating that persons Motor abnormalities have also been demonstrated by a number of studies, with dopamine dysregulation a suggested mechanism , MacManus et al, 2011, Mittal et al, 2011 Further work will be necessary in terms of neuro-genetics, imaging, electrophysiology and cognition to understand the ways in which psychotic symptoms contribute to a wide range of psychopathology in general and how these symptoms might contribute to psychosis in particular.…”
Section: Discussionmentioning
confidence: 93%